Signal Processing, Sensor/Information Fusion, and Target Recognition XXX 2021
DOI: 10.1117/12.2587994
|View full text |Cite
|
Sign up to set email alerts
|

CalibDNN: multimodal sensor calibration for perception using deep neural networks

Abstract: Current perception systems often carry multimodal imagers and sensors such as 2D cameras and 3D LiDAR sensors. To fuse and utilize the data for downstream perception tasks, robust and accurate calibration of the multimodal sensor data is essential. We propose a novel deep learning-driven technique (CalibDNN) for accurate calibration among multimodal sensor, specifically LiDAR-Camera pairs. The key innovation of the proposed work is that it does not require any specific calibration targets or hardware assistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The calibration results of the model were evaluated using the KITTI raw dataset, as shown in Tables 2 and 3. It shows a comparison of the performance in rotation and translation errors compared to RegNet [10], CalibNet [12], CalibDNN [29], and CFNet [30], where CFNet [30] denotes the 'stateof-the-art' deep learning method on the target-less LiDARcamera calibration problem. To estimate extrinsic calibration parameters, these methods utilize different networks that are trained with varying deviations of miscalibration.…”
Section: Results and Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration results of the model were evaluated using the KITTI raw dataset, as shown in Tables 2 and 3. It shows a comparison of the performance in rotation and translation errors compared to RegNet [10], CalibNet [12], CalibDNN [29], and CFNet [30], where CFNet [30] denotes the 'stateof-the-art' deep learning method on the target-less LiDARcamera calibration problem. To estimate extrinsic calibration parameters, these methods utilize different networks that are trained with varying deviations of miscalibration.…”
Section: Results and Evaluationsmentioning
confidence: 99%
“…Yuan et al [13] showed RGGNet, which considers the tolerance loss function, to achieve calibrated parameters by leveraging Riemannian geometry. Zhao et al [29] proposed a DNN architecture that is lightweight with a single iteration to obtain a calibration transformation by maximizing the consistency of mutlimodal data. Its performance can be refined using a training model with multiple iterations of different miscalibration ranges.…”
Section: B Target-less Approachmentioning
confidence: 99%
“…CMRNet [20] is an approach for locating a camera in a LiDAR-Map, and it is the first method to use the correlation layer of PWC-Net [21] to match features acquired from two sensors to achieve 6-DoF extrinsic calibration. CalibRCNN [12] used the constraint relationship between successive frames for calibration, which improved the accuracy, and CalibDNN [13] added geometric and transformation supervisions to solve the calibration problem and applied the method on a challenging dataset.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…3. The proposed method has a key advantage, namely, the multiresolution representations extracted from the backbone are semantically stronger than in prior methods [11]- [13]. Furthermore, the high-resolution representations are spatially accurate.…”
Section: B Network Architecture 1) Feature Extraction Networkmentioning
confidence: 99%
“…We consider the case where the autonomous sensing platform is composed of a set of RGB cameras and LiDAR sensors moving unconstrainedly in urban/terrain environments. Under this condition, the data streams of RGB video and LiDAR point clouds are collected in real time and then fed into a downstream system for data preprocessing, calibrating, and converting the 3D point clouds to 2D depth image 30 that results in pair of RGB-D data stream registered in a common coordinate frame. Given the pair of RGB-D data, our segmentation module performs feature detection, data fusion, segmentation, and pixel-level annotation automatically in an end-to-end fashion.…”
Section: Introductionmentioning
confidence: 99%